Black race is independently associated with underutilization of transplantation for clinical T1 hepatocellular carcinoma. Issue 6 (June 2022) - Sugumar, Kavin; Markt, Sarah C.; Hue, Jonathan J.; Hoehn, Richard S.; Lee, Richard T.; Chavin, Kenneth D.; Rothermel, Luke D.; Winter, Jordan M.; Hardacre, Jeffrey M.; Ammori, John B.; Ocuin, Lee M.
Abstract: Background: Hepatocellular carcinoma (HCC) is a leading cause of cancer mortality. Operative management of early disease includes ablation, resection, and transplantation. We compared the operative management of early-stage HCC in patients stratified by race. Methods: We identified patients with cT1 HCC and Charlson-Deyo score 0–1 in the National Cancer Database (2004–2016). We compared operative/non-operative management by race, adjusting for clinicodemographic variables. We performed marginal standardization of logistic regression to ascertain adjusted probabilities of resection or transplantation in patients under 70 years of age with insurance. Results: A total of 25, 029 patients were included (White = 20, 410; Black = 4619). After adjusting for clinico demographic variables, Black race was associated with a lower likelihood of undergoing operative intervention (OR 0.89, p = 0.009). Black patients were more likely to undergo resection (OR 1.23, p < 0.001) and less likely to undergo transplantation (OR 0.60, p < 0.001). Marginal standardization models demonstrated Black race was associated with increased probability of resection in patients >50yrs, with private insurance/Medicare, and lower probability of transplantation regardless of age or insurance payor. Conclusion: Black race is associated with lower rates of hepatic transplantation and higher rates of hepatic resection for early HCC regardless of age or insurance payor. The etiology of these disparities is multifactorial and correcting the root causes represents a critical area for improvement.